Thinking to transform : reflection in leadership learning - Volpe White, Jillian M.; Guthrie, Kathy L.; Torres, Maritza (Contemporary perspectives on leadership learning., 2019)
"In an era of constant connection, it can be challenging to prioritize time for reflection. Taking time to think can feel like a luxury or even a waste time. People facilitating complex leadership processes may feel the least able to pause and reflect. However, it is through intentional reflection that we make meaning of experiences, connect ideas, question assumptions, and generate innovative possibilities. By taking time to reflect, individually and with others, learners can see the full picture of an experience, understand their thought processes, and enhance their capacity for leadership. Beyond individual reflection, by engaging in reflection on social issues with others, leaders can be empowered and enabled to create positive changes. This book is a clarion call for educators and learners to make reflection a central priority. Reflection, the process of making meaning of experience, and leadership, a relational process for affecting change, are enhanced by one another. Together, they strengthen the potential for leadership learning through experience. This book addresses challenges for reflection in leadership learning while also connecting it to timely topics. It begins with connections between reflection and leadership and then introduces a framework for reflection in leadership learning. Reflection is a powerful strategy curricular and co-curricular learning; for instruction and assessment, reflection in leadership learning can benefit from both intentional framing and feedback. As socially constructed concepts, both reflection and leadership have historically lacked clarity; to add to the confusion, critical reflection is often interchanged with reflection. This book introduces a continuum of critical reflection in leadership learning. In order to facilitate reflection in leadership learning, educators must engage in the inner work of becoming reflective educators. Finally, in the face of complex social challenges, reflection, leadership, mindfulness, and resilience are juxtaposed in order to highlight how these concepts are reliant upon one another. Reflection in leadership learning is essential for anyone who wants to develop their capacity for leadership. When faced with complex social issues and challenges at a global scale, the only way to make progress is through collective action that results from critical reflection. To develop more resilient and mindful learners who can adapt to changing circumstances, educators must center reflection in leadership learning as a philosophy, pedagogy, outcome, and strategy. This book provides a balance of theory and practice to empower and enable educators to engage in reflective leadership learning"--